Problematizing the right to education in Brazil (Revista Direitos Humanos e Democracia, 2024)
This is a literature search regarding the right to education in Brazil, in the context of the Covid-19 pandemic, when the institutionalized teaching and learning process was carried out through Emergency Remote Learning. Our goal is to problematize the denouncing perspective that this teaching strategy does not guarantee the right to education at this moment, since face-to-face teaching and remote teaching are distinct. In order to it, we realize a literary review on the construction of the right to education, based on Bobbio (2004), Boto (2005), and on the Brazilian educational legislation; and a bibliographical review that allowed us to find four studies by educators who approached the right to education in times of pandemic. While two theoretical studies were negative about the guarantee of the right to education in the Emergency Remote Learning, mainly due to the large national educational inequalities, another theoretical study was cautious, placing prerequisites for this guarantee. The case study, based on the investigated experience, positioned itself positively towards guaranteeing the right to education in this new process in an emergency. After the analysis of the studies cited, we noticed the lack of perception that in-person and remote education are distinct schooling processes, which need to be qualified according to their structural, functional, didactic-pedagogical and circumstantial conjunctures, otherwise, we run the risk of a naive and unfair comparison with the school's performance in this period.
Keywords: right to education; emergency remote teaching; educational politics